PENTINGNYA KONSELING KARIR PADA KEGIATAN PKK - Linda Fitria; Mega Iswari; Afdal Afdal (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This article describes the importance of career guidance in PKK activities. Career guidance is a guidance activity in preparing to face the world of work, in choosing employment or certain positions / professions as well as equipping themselves to assume that position, and in adjusting to the various demands of the job fields entered. Empowerment of Family welfare includes all efforts of Guidance, Coaching and Empowerment so that families can live prosperously, progressively and independently. PKK has a role to help the village and village government in improving welfare towards the realization of a cultured, prosperous, developed, independent and harmonious family and has a role in developing the potential and role of women in increasing family income. In carrying out work programs in order to achieve the ideal goals, the need for career guidance in PKK activities.